Peran Kepemimpinan Kepala Sekolah Terhadap Profesionalisme Guru Pasca Sertifikasi di SMP Negeri I Pundong Bantul Yogyakarta - Nur Hidayatun (Pedir Research Institute, 2022)
This study aims to determine the role of leadership as well as supporting and inhibiting factors for school principals towards the professionalism of post-certified teachers at SMP N I Pundong Bantul Yogyakarta. This research is a qualitative research. The writer used qualitative research to explain the data that the writer got from the results of observations, interviews and documentation that the writer did in the field. In data analysis, researchers used Miles and Huberman's data analysis, which consisted of reduction, data presentation, drawing conclusions, and verification. In testing the validity of the data, researchers used a method and source triangulation technique. The results showed that post-certification professionalism at SMP Negeri 1 Pundong Bantul Yogyakarta was seen from 3 aspects, namely, having DIII/S1 academic qualifications, judging from the academic qualifications of the 20 post-certification teachers that the authors examined, class teachers had bachelor degrees strata 1 (S1) there are only 2 teachers who still have DIII/BA qualifications. Have an educator certificate in accordance with the field. Having competence, of the 20 post-certification teachers that the author examined, overall the teachers have mastered 4 competencies well where the four competencies that must be possessed by teachers are: pedagogic competence, personal competence, social competence and professional competence. Supporting factors for the leadership of the principal for post-certification teacher professionalism at SMP N 1 Pundong Bantul Yogyakarta, namely the existence of certification allowances that have been obtained by teachers, can increase enthusiasm and high discipline and build cooperation (cohesiveness) at work. While the inhibiting factor for the head of SMP N 1 Pundong Bantul Yogyakarta is the large burden on teachers with administration that must be met by teachers. Haven't tested the importance of technological media in adequate learning. The establishment of a building across the street makes it less intensive in supervision, student background influences student achievement, limited time to supervise teachers in the teaching and learning process.